The Moderating Effect of ROA on the Influence of CSR and GCG on Firm Value (Study of The Banking Sector in ASEAN Stock Exchange During Pandemic): Study of The Banking Sector in ASEAN Stock Exchange During Pandemic - Agnes Avelina; Sugeng Hariadi (Universitas Islam Lamongan, 2023)
This study aims to determine the effect of CSR and GCG proxied by Managerial Ownership and Institutional Ownership on Firm Value with Financial Performance proxied by ROA as a Moderating Variable.The population in this study was obtained using a purposive sampling technique for banking companies listed on the Indonesia, Malaysiaand Thailand Stock Exchange during the 2020-2021 period so that 26 companies were obtained as the research sample. The analytical method used is MRA with the help of the SPSS 26. The results of this study are that CSR and KI has no significant effect on firm value. KM has a significant effect on firm value. Financial performance cannot moderate CSR on firm value. Financial performance cannot moderate KM and KI on firm value.